2012
DOI: 10.1039/c2cp41838j
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control theory – closing the gap between theory and experiment

Abstract: Optimal control theory and optimal control experiments are state of the art tools to control quantum systems. Both methods have been demonstrated successfully for numerous applications in molecular physics, chemistry and biology. Modulated light pulses could be realized, driving these various control processes. Next to the control efficiency, a key issue is the understanding of the control mechanism. An obvious way is to seek support from theory. However, the underlying search strategies in theory and experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 134 publications
(234 reference statements)
0
90
0
Order By: Relevance
“…However, these values are not good enough to allow fault-tolerant quantum computation, which requires the gate fidelity > 99.9% [27]. One of the strategies to increase the fidelity is to apply more complex coherent control techniques such as optimal control [28] and genetic [29] algorithms to shape laser pulses. Optimal control of STIRAP based blockaded controlled phase gate has been analyzed recently in [20], where it was shown that the gate error can be decreased by an order of magnitude (from 10 −3 to 10 −4 ) if one uses optimized pulse sequences instead of analytic.…”
Section: Controlled Phase Gate Using Arp Excitation To Double Rydmentioning
confidence: 99%
“…However, these values are not good enough to allow fault-tolerant quantum computation, which requires the gate fidelity > 99.9% [27]. One of the strategies to increase the fidelity is to apply more complex coherent control techniques such as optimal control [28] and genetic [29] algorithms to shape laser pulses. Optimal control of STIRAP based blockaded controlled phase gate has been analyzed recently in [20], where it was shown that the gate error can be decreased by an order of magnitude (from 10 −3 to 10 −4 ) if one uses optimized pulse sequences instead of analytic.…”
Section: Controlled Phase Gate Using Arp Excitation To Double Rydmentioning
confidence: 99%
“…Therefore, several experimental and theoretical studies have since been carried out on diatomic molecules. [25][26][27][28][29] De VivieRiedle extended the concept theoretically to larger molecular systems by studying in reduced dimensionality the effect of the initial conditions on the subsequent dynamics: 30,31 it was suggested to control the relative phases and amplitudes of a superposition of electronic states near a conical intersection to "steer" chemical reactions and control the branching ratio of populations for instance. Using the Ehrenfest method, we have previously investigated the nature of the nuclear motion when an electronic wave packet is populated in benzene and toluene cations: 32,33 we have shown that manipulation of the details of the electronic wave packet (relative weight and phase) leads to the control of the initial nuclear motion.…”
Section: Introductionmentioning
confidence: 99%
“…and is not directly relevant for control. quantum phenomena or quantum optical control could then be adapted [36][37][38][39]. Light-induced C.I., created in molecules with the help of external laser fields, could be used to control the position of the intersection and the strength of the nonadiabatic coupling [40,41].…”
Section: Note That Trðρmentioning
confidence: 99%